Current state of antimicrobial stewardship and organ transplantation in Spain. Issue 5 (18th October 2022) - Silva, Jose Tiago; Aguado, José María
Abstract: Introduction: Solid‐organ transplantation (SOT) remains the best therapeutic option for end‐stage organ disease. Regrettably, SOT recipients are disproportionately affected by nosocomial infections produced by multidrug‐resistant (MDR) microorganisms and antimicrobial adverse events. Both have a negative impact on the patient´s outcome. Methods: Description of data concerning the antimicrobial stewardship program (ASP) in SOT recipients of the University Hospital "12 de Octubre", and review of other Spanish ASPs. Results: From May 2017 to December 2021, the ASP issued 2.785 recommendations. Approximately, 4.9% were aimed at improving the antimicrobial treatment administered to SOT recipients. Treatment discontinuation or change to a better therapeutic regimen was recommended in 51.8% and 26.3% of cases, respectively. The acceptance rate of the recommendations was close to 92%. Between June 2015 and March 2016, a quasi‐experimental study consisting of a joint ASP and hospital‐acquired infection control (HAIC) initiative, which included kidney transplant recipients, reported a significant reduction in the consumption of meropenem, vancomycin and ciprofloxacin, and a reduction in the incidence of global bacterial infections, upper urinary tract infections, and cystitis. Although Spain has several robust regional ASPs (e.g., VINCat and PIRASOA), data specifically concerning SOT patients is lacking. Conclusion: ASP coupled with HAIC programs have proven to be effective in SOT, and should be implemented in centers that perform transplantation. Since data is scarce, Spanish centers which have ASP should report their experience in SOT. Understanding the efficacy and safety of the Spanish ASP´s intervention in the SOT population is essential and deserves further study.